High initiation and long duration of breastfeeding despite absence of early skin-to-skin contact in Karen refugees on the Thai-Myanmar border: a mixed methods study. - White, A; Carrara, V; Paw, M; Malika; Dahbu, C; Gross, M; Stuetz, W; Nosten, F; McGready, R (2012)
UNLABELLED: BACKGROUND: Early skin-to-skin contact (SSC) after birth is recommended as part of the United Nations Children's Fund (UNICEF) baby friendly health initiative to promote optimum breastfeeding. This paper reports rates of breastfeeding initiation and duration in a low resource environment, where early SSC is not practised, and explores views of pregnant women and midwives surrounding breastfeeding and swaddling. METHODS: Data from records from a single hospital on the Thai-Myanmar border where refugee women gave birth during a one-year period (2010) were used to determine breastfeeding initiation rates and the time of the first breastfeed, and duration of breastfeeding of the previous alive child in multigravidae. Focus group discussions (FGD) were conducted to obtain information from pregnant women attending antenatal care about their intended or previous duration of breastfeeding and views on breastfeeding. Interviews with local midwives explored reasons for high rates of breastfeeding in this setting and the practice of newborn swaddling. RESULTS: Of 1404 live births in 2010 in Maela refugee camp there were 982 evaluable mother-newborn pairs, including 80 infants born before 37 weeks gestation. Initiation of breastfeeding within the first hour after birth and exclusive breastfeeding at discharge in term mother-newborn pairs was 91.2% (823/902) and 99.3% (896/902); and before 37 weeks gestation, 48.8% (39/80) and 98.8% (79/80). Reported duration of previous breastfeeding was 19 (range 2 to 72) months.During FGD all primigravidae (n = 17) intended to breastfeed and all multigravidae (n = 33) had previously breastfed; expected or previous duration of feeding was for more than one year or longer. The major theme identified during FGD was breastfeeding is "good". Women stated their intention to breastfeed with certainty. This certainty was echoed during the interviews with midwifery staff. SSC requires a delay in early swaddling that in Karen people, with animistic beliefs, could risk loss of the spirit of the newborn or attract malevolent spirits. CONCLUSIONS: In a population with a strong culture of breastfeeding and robust breastfeeding practices, high rates of initiation and duration of breastfeeding were found despite a lack of early skin-to-skin contact. Local preferences, traditions and practices that protect, support and maintain high rates of breastfeeding should be promoted.